PENGARUH MEDIA AUGMENTED REALITY BERBANTU ASSEMBLR EDU TERHADAP PEMAHAMAN KONSEP MATEMATIKA SISWA DI KELAS IV SDN PEMEPEK TAHUN AJARAN 2025-2026 - Dian Mekhrani; Alwan Mahsul; Siti Ruqoiyyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of augmented reality media assisted by assemblr edu on students’s understanding of mathematical concepts in fourth grade at SDN Pemepek on solid geometry material. This study employed a quantitative approach with a quasi-experimental research design. The sample was selected using a saturated sampling technique, consisting of two classes, namely class IV A as the experimental class and class IV B as the control class. Data were collected through tests and observations. Observations were conducted using observation sheets, while the tests consisted of pretest and posttest designed to measure seven indicators of conceptual understanding. The results showed that the mean score of the experimental class (76.90) was higher than that of the control class (68.07). Based on hypothesis testing using an independent sample t-test, the p-value obtained was 0.021 < 0.05; therefore, Ha was accepted. These findings indicate that the implementation of Augmented Reality media assisted by Assemblr Edu has a significant effect and provides a strong positive impact on students’ understanding of mathematical concepts.